A Platform for High‐Throughput Assessments of Environmental Multistressors. Issue 4 (24th January 2018) - Nguyen, Brian; Graham, Percival J.; Rochman, Chelsea M.; Sinton, David
Abstract: A platform compatible with microtiter plates to parallelize environmental treatments to test the complex impacts of multiple stressors, including parameters relevant to climate change and point source pollutants is developed. This platform leverages (1) the high rate of purely diffusive gas transport in aerogels to produce well‐defined centimeter‐scale gas concentration gradients, (2) spatial light control, and (3) established automated liquid handling. The parallel gaseous, aqueous, and light control provided by the platform is compatible with multiparameter experiments across the life sciences. The platform is applied to measure biological effects in over 700 treatments in a five‐parameter full factorial study with the microalgae Chlamydomonas reinhardtii . Further, the CO2 response of multicellular organisms, Lemna gibba and Artemia salina under surfactant and nanomaterial stress are tested with the platform. Abstract : A high‐throughput experimental platform capable of investigating environmental multistressors is demonstrated. Adapting a long‐range gradient generator and a projector to microtiter plates enables experiments with parallel control of multiple gaseous, aqueous, and light parameters. The platform is compatible with experiments involving microorganisms, as well as experiments with small multicellular plants and animals.